PENGELOLAAN USAHA MANDIRI SEKOLAH DALAM PENINGKATAN KUALITAS PENDIDIKAN - Angga Kurniawan; Maisyaroh Maisyaroh; Djum Djum Noor Benty (Universitas Negeri Malang, 2019)
Abstract: The purpose of this study is to provide the information of management school independent businesses in school. This research used the qualitative approach with case studies types. Data collection tecniques used are interviews, observation, and documentation. The process of data analysis are data condensation, data display, and conclusion drawing/verification. The result of this research: there are 3 types of school independent businesses, namely school waste banks, business center school, and car air conditioning workshops; has collaboration with the industries namely Bank Sampah Malang, eSWe, Aice, Unggul, and Auto 2000; school independent businesses impacts are school be famous, the needs of students and school residents are fulfilled, and school has the tools and location for practice; the supporting factors of the school independent businesses are based on the need relating to late payment of tuition fees, learning and teaching processes, and government programs, inhibiting factors of the school independent business are the arrival of the rainy season and holiday, violations committed, and the administration system that not good enough, and the solution used are by temporarily closing independent school businesses, do the supervising, and fix the system.Keywords: management, school independent business Abstrak: Tujuan penelitian ini adalah memberikan informasi pengelolaan usaha mandiri di sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Proses analisis data dengan data condensation, data display, dan conclusion drawing/verification. Hasil penelitian ini: terdapat 3 jenis usaha mandiri sekolah yaitu bank sampah sekolah, business center school, dan bengkel AC mobil; menjalin kerjasama dengan pihak industri yaitu Bank Sampah Malang, eSWe, Aice, Unggul, dan Auto 2000; dampak usaha mandiri sekolah yaitu sekolah menjadi terkenal, kebutuhan peserta didik dan warga sekolah terpenuhi, serta memiliki alat dan lokasi untuk praktik; faktor penunjang usaha mandiri sekolah yaitu adanya keterlambatan pembayaran SPP, kebutuhan peserta didik dan warga sekolah, dan program pemerintah; faktor penghambat usaha mandiri sekolah yaitu datangnya musim hujan dan liburan, adanya pelanggaran, dan sistem administrasi yang kurang baik; dan solusi yang dilakukan yaitu dengan cara menutup sementara usaha mandiri sekolah, melakukan pengawasan, dan memperbaiki sistem.Kata Kunci: pengelolaan, usaha mandiri sekolah